Engineered cellulose hydrogels: multifunctional platforms for innovative stomatological therapies and precision medicine - Zhang, Junyang; Zhao, Rui; Zhang, Xiyue; Dong, Fanqiao; Zhang, Yikun; Liu, Di; Meng, Shuyu; Wang, Ai; Liu, Siyu (Frontiers in Materials, 2025)
Cellulose, as a natural material, serves as an excellent raw material for creating antimicrobial biological materials due to its unique nanostructure for cell scaffolds, customizable mechanical properties, biodegradability, and biocompatibility. The cellulose hydrogel offers exceptional structural adjustability and functional design options, thanks to the abundance of hydroxyl groups on its surface, making it suitable for various applications in tissue engineering, biomedicine carriers, wound dressings, and more. Despite its potential in stomatology, the research progress in this area remains unclear. This review focuses on the performance criteria for ideal cellulose-based hydrogels, including self-healing, adhesion, antibacterial properties, and drug delivery. It also covers preparation methods, repair mechanisms, and applications in biomimetic remineralization for hard tooth tissues, periodontitis, dental body repair, alveolar bone repair, and more. Persistent challenges—including scalable manufacturing processes, cost-effective production of functionalized variants, long-term biological safety assurances, antimicrobial resistance management, and ecological sustainability require resolution. Concurrently, establishing standardized regulatory protocols for clinical translation warrants prioritized efforts. By aligning material innovations with unresolved clinical demands in dental care, this review positions cellulose hydrogels as foundational components for personalized stomatological interventions, accelerating the transition toward precision-oriented dental therapeutics.